The role of transformational leadership on innovative work behavior: A moderated-mediation study - Az Zahra, Afifah Chusna; Etikariena, Arum (Faculty of Psychology, Universitas Diponegoro, 2024)
Background: Innovative work behavior is crucial in enhancing governmental organizations' efforts to community services. Innovation among employees could be enhanced by transformational leadership that fosters a sense of meaningful work. However, the effectiveness may be moderated by the power distance culture within the organization.Purpose: This study explores the relationship of transformational leadership and innovative work behavior through mediator and moderator mechanisms.Method: 125 civil servants at government organizations X and Y in Indonesia participated by completing Innovative Work Behavior Scale (α = .96), Multifactor Leadership Questionnaire (α = .96), The Work and Meaning Inventory (α = .86), and the Power Distance Scale (α = .84) distributed online. Moderated mediation effects were analyzed using PROCESS.Findings: Analysis showed that transformational leadership was not related to innovative work behavior, but meaningful work was found to mediate the influence of transformational leadership on innovative work behavior (β = 0.217, SE = 0.079, 95% CI [0.069, 0.382]). However, power distance culture did not moderate these relationships directly or indirectly.Implication: This study provides empirical evidence regarding the role of transformational leadership on employee innovative work behavior and the role of individual and group-level variables. The findings also underscore the importance of meaningful work design to improve employee innovative work behavior.